The Intervening of Earning Management to Tax Aggressiveness in Indonesian Consumer Non-Cyclical Companies - Wiwit Irawati; Aris Sanulika; Dian Widiyati; Rosita Wulandari (Jurnal Kajian Akuntansi, 2025)
The purpose of this study is to deepen understanding of how sales growth and capital intensity affect corporate tax aggressiveness through profit management practices, especially in the non-cyclical consumer sector which is stable and crucial to the economy. The results of the research can be used as a reference to improve tax supervision and encourage transparency and corporate governance in the capital market, especially in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX). This study uses a sample of 238 data from 34 non-cyclical consumer companies during the 2017-2023 period. The data analysis process was carried out using the EViews application through a quantitative approach and the type of intervening research. The results of the study show that there is a positive influence of sales growth and capital intensity on tax aggressiveness. Meanwhile, tax aggressiveness is positively influenced by capital intensity and negatively influenced by sales growth. Another result is evidence that profit management does not affect tax aggressiveness, nor does it mediate the relationship between sales growth and capital intensity partially to tax aggressiveness.